Travelling words : circulation of pedagogical knowledge in textbooks (Brazil/Portugal, from mid‑nineteenth century to the mid‑twentieth century) - Vera Teresa Valdemarin; Vera Lúcia Gaspar da Silva (Revista Brasileira de História da Educação, 2017)
[...]